Seasonal plankton dynamics in Kongsfjorden during two years of contrasting environmental conditions. (April 2023) - Assmy, Philipp; Cecilie Kvernvik, Ane; Hop, Haakon; Hoppe, Clara J.M.; Chierici, Melissa; David T., Divya; Duarte, Pedro; Fransson, Agneta; García, Laura M.; Patuła, Weronika; Kwaśniewski, Sławomir; Maturilli, Marion; et al.
Highlights: Selective copepod grazing and water mass origin impacted spring bloom composition. Diatom bloom enhanced zooplankton recruitment and deep carbon export. Spring bloom composition impacted summer plankton community. Mixo- and heterotrophic protists dominated the nutrient-poor summer months. Copepod grazers controlled the summer protist community. Abstract: Seasonal plankton time-series data are presented from Kongsfjorden from two years with contrasting environmental conditions. Kongsfjorden (west coast of Spitsbergen – 79°N) integrates inputs from Atlantic and Arctic waters, and glacier run-off, and is thus a prime location to study impacts on ecosystem dynamics of key environmental drivers that are relevant across the Arctic. Despite extensive research in Kongsfjorden, seasonally-resolved data are scarce. From late April/early May to early September 2019 and 2020, we conducted pelagic sampling at a mid-fjord station at mostly weekly to bi-weekly resolution investigating the environmental drivers of phyto- and zooplankton community composition and phenology. During spring 2019, Atlantic water masses with temperatures > 1 °C were found throughout the upper 250 m of the water column, and little sea ice occurred in the fjord. Spring 2020, in turn, was characterized by the presence of local water masses with sub-zero temperatures and relatively extensive sea-ice cover. The most striking contrast between the two years was the difference in phytoplankton spring bloom composition. In 2019, the spring bloom was dominated by the colonial stage of the haptophyte Phaeocystis pouchetii and diatoms played a minor role, while the spring bloom in 2020 was dominated by diatoms of the genus Thalassiosira succeeded by P. pouchetii . Selective grazing by large copepods and water mass structure seem to have been the decisive factors explaining the marked difference in diatom spring bloom biomass between the years while similar spring abundances of P. pouchetii in both years indicated that this species was less impacted by those factors. Our data suggest that differences in spring bloom composition impacted trophic transfer and carbon export. Recruitment of the dominant copepods Calanus finmarchicus and C. glacialis, Cirripedia and euphausiid larvae as well as the export of carbon to the seabed was more efficient during the diatom-dominated compared to the P. pouchetii– dominated spring bloom. In summer, the plankton composition shifted towards a flagellate-dominated community characterized by mixo- and heterotrophic taxa adapted to a lower nutrient regime and strong top-down control by copepod grazers. However, residual silicic acid after the P. pouchetii– dominated spring bloom fueled a late summer diatom bloom in 2019. Our data provide a first glimpse into the environmental drivers of plankton phenology and underline that high-resolution monitoring over many annual cycles is required to resolve the ephemeral variations of plankton populations against the backdrop of climate change.